Does Business Advisory Help? – The SMEs Dilemma in Malaysia Livestock Industry - Fakhrul Anwar, Zainol; Nalini, Arumugam; Nor Asmahani, Ibrahim; Wan Norhayate, Wan Daud (2014)
NMF Company (NMF) is a manufacturing and trading company which operated since 2008 in Kuala Terengganu, Terengganu, Malaysia. NMF offers ruminant feed products such as pallets, pallet feeder cattle and dairy cattle feed pallets. From the beginning of its establishment, the company faced various challenges and obstacles; from operation up to human resources related issues. Though, having good products and have been recognized by the Ministry of Agriculture (MOA) and HALAL certification from JAKIM (Malaysian Halal Certification Authority), it did not favour the company in capturing the market share in the industry. Despite various action being taken by the management, it seem not enough for the company to moving forward. Thus, the company is looking other alternatives to resolve all the issues. This case study examines NMF’s operational challenges within SMEs context and how the company can benefits from the business advisory services offered by various parties.